IMPLIKASI PENGELOLAAN GALIAN C TERHADAP LINGKUNGAN HIDUP DI WILAYAH NGORO KABUPATEN JOMBANG DALAM PERSPEKTIF PERATURAN DAERAH KABUPATEN JOMBANG NOMOR 8 TAHUN 2017 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP DAN HUKUM ISLAM - H. Noho, Muhammad Dzikirullah; Azhar, Nurul (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2022)
This article intends to find out the management of excavation C on the environment in the Ngoro Jombang area and its implications according to Regional Regulation Number 8 of 2017 concerning Protection and management of the environment and fiqh biah. The location of this research is located in Ngoro District, Jombang Regency. This research is included in qualitative research. To obtain data, researchers directly obtain from the source without intermediary other parties, which are then processed. In this study there are two sources of data, namely primary and secondary data sources. Collecting data by means of interviews, observation, documentation. After the data is collected, to analyze it using descriptive method. The results obtained from the data analysis are that the management of excavation c is mining which includes: sand, gravel, the process of which is by dredging the soil to make holes in it for profit, in this activity the impact is not only on local residents, but also on the earth and the surrounding nature. In the law and fiqh biah itself, it is allowed on the condition that it should not be excessive and damage the surrounding nature just to meet the needs and prosperity of the community. Keywords: Environmental protection and management, Fiqh biah